Coping style and posttraumatic growth among adult survivors 8 years after the 2008 Wenchuan earthquake in China. (1st June 2017) - Guo, Jing; Fu, Mingqi; Xing, Jia; Qu, Zhiyong; Wang, Xiaohua
Abstract: The objectives of the present study were to identify the relationship between coping style and PTG among survivors 8 years after the Wenchuan earthquake, using data from a cross-sectional survey. 1369 participants were recruited from two different sites in the areas that were severely affected by the earthquake. Bivariate correlation analysis and multivariate linear regression analysis were used to assess PTG and identify associated factors. The results indicated that both positive and negative coping style can develop to PTG among adult survivors 8 years later after Wenchuan earthquake. Positive coping style had a higher correlation with "new possibilities" (β = 0.19, p < 0.001), "personal strength" (β = 0.30, p < 0.001) "appreciation of life" (β = 0.11, p < 0.001) than negative coping style, while negative coping style had a higher correlation with "relating to others" (β = 0.25, p < 0.001) than positive coping style. In addition, the study found PTSD and PTG co-exist after the earthquake, while depression was a barrier factor during the process of developing PTG. Highlights: Both negative and positive coping style have a relatively high correlation with PTG. PTSD and PTG co-exist among adult survivors after earthquake Depression is a barrier factor during the process of developing PTG. Female, low SES, older people are less likely to develop PTG.